The effect of alloying in Pt-Sn/C electrocatalysts in the performance of a direct ethanol fuel cell - Colmati, F.; Sousa, R. de; Ciapina, E. G. [UNESP]; Gonzalez, E. R. (Electrochemical Soc Inc, 2014)
Work on Pt-Sn-C catalysts for ethanol oxidation showed that a thermal treatment at moderate temperatures leads to a significant increase in activity. The best activity was observed for Pt3Sn1 thermally treated at 200 degrees C and ascribed to a Pt3Sn1 phase plus a cleaning effect. However, electronic effects may be very important and these were not evaluated in the Pt3Sn1 phase. Therefore, in this work we investigated the effect of the degree of alloy on the electronic structure of Pt3Sn1 electrocatalysts by performing electrochemical in situ X-ray absorption (XAS) experiments in the Pt L-III XANES region. Overall, the results show that although the occupancy of the Pt 5d band depends on the degree of alloy other factors, such as the presence of tin oxides/hydroxides in the materials, have to be considered to understand the performance of the DEFC.